2014
DOI: 10.4269/ajtmh.13-0542
|View full text |Cite
|
Sign up to set email alerts
|

Defining Risk Groups to Yellow Fever Vaccine-Associated Viscerotropic Disease in the Absence of Denominator Data

Abstract: Abstract. Several risk groups are known for the rare but serious, frequently fatal, viscerotropic reactions following live yellow fever virus vaccine (YEL-AVD). Establishing additional risk groups is hampered by ignorance of the numbers of vaccinees in factor-specific risk groups thus preventing their use as denominators in odds ratios (ORs). Here, we use an equation to calculate ORs using the prevalence of the factor-specific risk group in the population who remain well. The 95% confidence limits and P values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Our data also establish IFNAR1 deficiency as the first genetic etiology for YEL-AVD, and as its first explanation ( Seligman et al, 2014 ). Despite the development of the YF vaccine in the 1930s, YFV remains a global health threat partially due to deficient rates of vaccination.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our data also establish IFNAR1 deficiency as the first genetic etiology for YEL-AVD, and as its first explanation ( Seligman et al, 2014 ). Despite the development of the YF vaccine in the 1930s, YFV remains a global health threat partially due to deficient rates of vaccination.…”
Section: Discussionsupporting
confidence: 72%
“…A diagnosis of YF vaccine–associated viscerotropic disease (YEL-AVD) was made. She does not belong to any known risk groups for YEL-AVD ( Seligman et al, 2014 ). 1 yr after recovery, she remains healthy.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies of cellular immune signatures, comparing groups receiving different therapies and with various diseases, could help in understanding why patients with SLE and SpA had the lowest antibodies levels. Previous studies have shown that severe AE are more common in patients with AID, particularly SLE (8). Also, immunosuppressive drugs can increase the risk of AE (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…The 17DD-Yellow Fever (YF) vaccine induces safe and effective protective immunity in healthy individuals, resulting from robust humoral and cellular immune responses (1-3); however, it has been proposed that immune-compromised individuals mount suboptimal immunologic responses after vaccination (4)(5)(6). Moreover, some studies have pointed to a high prevalence of severe adverse post-vaccination events in patients with autoimmune diseases (AID), particularly systemic lupus erythematosus (SLE) and those receiving systemic corticosteroid therapy (7)(8)(9)(10). Studies assessing the safety, effectiveness, and immunogenicity of YF vaccination in immune-compromised patients, particularly those with AID, remain scarce (4).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors are age (young children under 6 months and adults over 50), pregnancy and immunodeficiency. Most SAEs concern primary vaccination [ 143 , 144 ]. Based on meta-analyses in many countries with reliable pharmacovigilance, the incidence of SAEs was estimated to be 11.1–15.6 per million vaccinated persons, including 6.6 YFV-AND and YFV –AVD cumulated, with wide variations depending on the country [ 145 ].…”
Section: Introductionmentioning
confidence: 99%